Synthesis and conductivity studies of poly (Methyl methacrylate) (PMMA) by co-polymerization and blending with polyaniline (PANi) - Abu Hassan Shaari, Helyati; Ramli, Muhammad Mahyiddin; Mohtar, Mohd Nazim; Abdul Rahman, Norizah; Ahmad, Azizan (MDPI AG, 2021)
Poly(methyl methacrylate) (PMMA) is a lightweight insulating polymer that possesses good mechanical stability. On the other hand, polyaniline (PANi) is one of the most favorable conducting materials to be used, as it is easily synthesized, cost-effective, and has good conductivity. However, most organic solvents have restricted potential applications due to poor mechanical properties and dispersibility. Compared to PANi, PMMA has more outstanding physical and chemical properties, such as good dimensional stability and better molecular interactions between the monomers. To date, many research studies have focused on incorporating PANi into PMMA. In this review, the properties and suitability of PANi as a conducting material are briefly reviewed. The major parts of this paper reviewed different approaches to incorporating PANi into PMMA, as well as evaluating the modifications to improve its conductivity. Finally, the polymerization condition to prepare PMMA/PANi copolymer to improve its conductivity is also discussed.